CONSTRAINTS ON SEISMIC VELOCITY ANOMALIES BENEATH THE SIBERIAN CRATON FROM XENOLITHS AND PETROPHYSICS - Kobussen A.F.; Christensen N.I.; Thybo H. (My University, 2006)
High seismic Vp velocity anomalies (8.7-9.0 km s- 1) have long been known about in regions of the uppermost mantle of the Siberian craton, often in association with kimberlite fields. Laboratory measurement of seismic properties of five xenoliths, three peridotites and two eclogites, from the Udachnaya kimberlite under confining pressures up to 600 MPa were extrapolated to uppermost mantle P-T conditions of 1500 MPa and 500 °C, however none of the velocities are high enough to explain the observations. Eclogites or peridotites are commonly considered to be the source of anomalous high velocities. We prefer a peridotitic source to an eclogitic source due to the unusual chemistry and regional uniformity of eclogitic garnets required, maximum velocity limitations on laboratory measurements of seismic properties of natural eclogites, and purported abundance of eclogites in the lithosphere. Alternatively, a highly depleted peridotite, such as dunite or harzburgite, can produce velocities high enough to match observations. Olivine petrofabrics in most peridotites, including the three peridotites used in this study, are great enough to produce the observed high velocities provided olivine petrofabrics are continuous enough and correctly oriented to be seismically detectable and the modal proportion of olivine is high. There have been suggestions by other authors that the Siberian upper mantle is highly depleted and that a lithosphere-scale shear zone exists, which may have acted to organize fabrics into segments large enough for detection. Anomalously high Vp-Vs velocity ratios of greater than 1.8 are expected parallel to the olivine [100] maxima required to be present in a high-velocity olivine-dominated upper mantle. Vp-Vs velocity ratios can serve as a means of inferring large-scale anisotropy when limited seismic data are available, as in Siberia. © 2006 Elsevier B.V. All rights reserved.
Keywords: ECLOGITE; LITHOSPHERIC MANTLE; PERIDOTITE; PETROFABRIC; SEISMIC ANISOTROPY; SIBERIA